PREFERENCE IN SELECTING THE CITY MAYOR ELECTION OF BENGKULU UNDER ETHNIC BACKGROUND - Rahimandani Rahimandani (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
This study  aims  to: first, to find and  analyze the correlation and  effect of ethnic background of the selecting preferences in the  mayor  election of Bengkulu City in 2012. Second, to find and  analyze whether there was a shift or change in preferences based on ethnic backgrounds in the elections of the Mayor of Bengkulu City between 2007 and2012.This study applied a quantitative approach that classified as causal explanatory descriptive and comparative study. This research is located in the  Bengkulu City by taking  a sample of 100 respondents by simple random sampling method. To answer the  first research objective, statistical analysis is used  multinomial logistic  regression analysis, whereas to answer the second research purposes used  non-parametric statistical analysis of the Mc Nemar test.The results of the  data  analysis shows  there are significance correlation and  influence of the  ethnic background with preference vote in the election of Mayor and  Deputy Mayor of Bengkulu City in 2012. Specifically,  ethnic background influence someone to choose candidate for Mayor and  Deputy Mayor from ethnic Serawai  - Minang, Serawai  - Beng- kulu City, and Serawai - Palembang. Then, there was a preference change to choose based on ethnic background in the elections of the city of Bengkulu in 2007 with the election in 2012. Voter preferences based on ethnicity has declined in2012 compared to 2007